Advanced Artificial Intelligence and Robo-Justice - Zekos, Georgios I. (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book deals with digital technology which is transforming the landscape of dispute resolution. It illustrates the application of AI in the legal field and shows the future prospect of robo-justice for an AAI society in the advanced artificial intelligence era. In other words, the present justice system and the influence of current AI upon courts and arbitration are investigated. The transforming role of AI on all legal fields is examined thoroughly by giving answers concerning AI legal personality and liability. The analysis shows that digital technology is generating an ever-growing number of disputes and at the same time is challenging the effectiveness and reach of traditional dispute resolution avenues. To that extent, the book presents in tandem the impact of AI upon courts and arbitration, and reveals the role of AAI in generating a new robo-justice system. Finally, the end of the perplexing relation of courts and arbitration is evidenced methodically and comprehensively.
Introduction -- Part I: Present Regulation of Courts And Arbitration And Their Paradox -- The Legal Basis of Courts & Arbitration -- Constitution, Courts And Arbitration -- Judges and Arbitrators As Law Makers -- Courts' Engagement In Arbitration Under US, English, Belgian And Greek Law -- AAI National Authority Management Arbitration -- Part II: Courts and Arbitration in The Advanced Artificial Intelligence Era -- From AI Towards Advanced AI -- From ADR to ODR -- Courts and Arbitration Advancements -- AI in Arbitration And Courts -- Robo-Justice -- Conclusions.
Keywords: Information technology-Law and legislation; Mass media-Law and legislation; Artificial intelligence; IT Law, Media Law, Intellectual Property; Artificial Intelligence